Chinese Herbal Medicine Combined with Intravitreal Antivascular Growth Factor Agents in Treatment of Macular Edema Secondary to Retinal Vein Occlusion: A Systematic Review and Meta-Analysis - Su Xiaojuan; Li Xiaodong; Fu Zhongmei; Ye Hejiang (Journal of Ophthalmology)
Background. Retinal vein occlusion (RVO) is the second most common retinal vascular disease in the world after diabetic retinopathy. Moreover, macular edema (ME) is the main cause of visual impairment in RVO patients. Intravitreal injection of antivascular endothelial growth factor (VEGF) agents is recommended for RVO-ME. However, repeated injections severely limit their efficacy. Chinese herbal medicine (CHM) is widely used in RVO-ME as adjuvant therapy in China. Objective. The study aims to evaluate the efficacy and safety of anti-VEGF combined with CHM for RVO-ME and to provide reliable evidence for clinical application. Methods. Seven databases were searched without language or publication status restrictions. Randomized controlled trials (RCTs) comparing anti-VEGF combined with CHM (anti-VEGF + CHM) versus anti-VEGF in participants with RVO-ME were included in this study. The “risk of bias assessment tool” of the Cochrane Handbook was applied to assess the quality of included trials, and RevMan 5.3 software was used for data analysis. Results. A total of 10 relevant trials with 743 patients were identified. The results showed that BCVA of the anti-VEGF + CHM group significantly improved at 3 months (P<0.00001), 6 months (P=0.008), and 12 months (P=0.01), and CMT significantly reduced at 1 month (P=0.02), 2 months (P=0.0009), 3 months (P<0.05), 6 months (P<0.0001), and 12 months (P<0.00001) compared with the anti-VEGF group alone. At the same time, the anti-VEGF + CHM group has a better performance in reducing the number of injections (P<0.05) and improving the total effective rate (P<0.0001). However, regarding adverse events, there was no statistical difference between the two groups (P=0.09). Conclusions. Our results provide promising evidence that anti-VEGF therapy combined with CHM may be more beneficial to patients than anti-VEGF therapy alone. However, because of the low quality and small sample size of the included studies, more rigorous and larger-scale trials were necessary to validate our results. Registration Number. CRD42021270262.